4He age discordance and release behavior of a double shell botryoidal hematite from the Schwarzwald, Germany - Wernicke, Rolf Stephan; Lippolt, Hans J. (Geochimica et cosmochimica acta, 1994)
Microprobe analyses of a double shell botryoidal hematite from the Fahlenbach vein system, (Schwarzwald, Germany) show an Fe3+ depletion of 3-4% with respect to Al3+ and silicon within a ~0.5 mm wide zone of alteration which separates both shells, and probably is the result of a subsequent hydrothermal event. Induced 235U fission tracks of grain mounts from both shells reveal several grain populations within a range of ~3 to ~22 ppm total uranium. Mass spectrometer- (U) and photometer analyses (Th) of various localities probed within each shell vary significantly at about 5 and 12 ppm U, as well as at 11 and 19 ppm Th. The ThU ratios vary from ~ 1.5 to ~2. 4He concentrations correlate with [U+(0.23)Th] heterogeneities which permits construction of two shell-internal isochrons. The 4He ages are discordant (inner shell, although mineralogically older: 150 Ma; outer shell: 182 Ma). 4He release by stepwise heating of one sample from each shell yielded activation energies of 124 ± 8 and 142 ± 7 [kJ/mol]. The extrapolated 4He diffusion coefficients at 20°C (logD20r2 values) of −19.7 ± 0.7 and −22.2 ± 0.6 [sec−1] reveal a higher 4He retentivity at earth's surface temperatures for the outer shell. 4He closure temperatures (after Dodson, 1973) are lower for the inner shell hematite by ~50°C, probably also indicating earlier opening during heating. The age discordance could be the result of a younger hydrothermal event which probably also has caused the observed alteration zone. Such an event is potentially related to the emplacement of the nearby Rappenloch hematite generation (II) 156 Ma ago. Complete rejuvenation of the inner shell hematite had occurred, whereas the 4He age of the outer shell was only slightly lowered due to the higher 4He retentivity.
Elektronische Reproduktion der Druck-Ausgabe 3. April 2003
Gesehen am 02.02.2023
Im Titel ist die Zahl "4" hochgestellt